Answer: A ∪ B = {a, b, c, d}
(A ∪ B) ∪ C = = {a, b, c, d, e}
B ∪ C = = {a, b, d, e}
(B ∪ C) ∪ A = = {a, b, c, d, e}
Explanation:
A = {a, b, c} B = {a, b, d} C = {b, d, e}
Union means "to join" so combine the sets to form a union.
A ∪ B = {A & B}
= {a, b, c & a, b, d}
= {a, b, c, d} because we do not need to list a & b twice
(A ∪ B) ∪ C = {(A ∪ B) & C)
= {a, b, c, d & b, d, e}
= {a, b, c, d, e} because we do not need to list b & d twice
B ∪ C = {A & B}
= {a, b, d & b, d, e}
= {a, b, d, e} because we do not need to list b & d twice
(B ∪ C) ∪ A = {(B ∪ C) & A)
= {a, b, d, e & a, b, c}
= {a, b, c, d, e} because we do not need to list a & b twice